(untitled) (Sustainability in Debate, 2021)
Due to the construction of the Itaparica Hydroelectric Plant in 1988, the Tuxás were displaced from their lands and resettled, generating internal conflicts and various socio-environmental impacts. Historically dedicated to agriculture and fishing, the resettlement of Tuxás changed their livelihoods, affecting nutrition and their relationship with their livelihoods. For those who still have access to fishing on the São Francisco River, the availability of fish has been reduced as a result of water polluting eutrophication, due to the disposal of sewage and fertilizers. The results include new elements, often disregarded, to reexplore the socio-environmental trade-offs of the installation of hydroelectric plants in Brazil. He concludes by proposing alternative perspectives (mainly from the bottom up), to rethink the delicate balance between economic progress driven by energy generation in Brazil and also the negative impact on the livelihood of the country’s most vulnerable communities.